ANALYZING STUDENT’S TEXT WITHIN CRITICAL THINKING, CRITICAL LITERACY, AND APPRAISAL THEORY FRAMEWORKS “DANGERS OF TEXTING WHILE DRIVING” - Anna Riana Suryanti Tambunan; Widya Andayani; Winda Setiasari; Fauziah Khairani Lubis (LINGUISTICA, 2019)
This paper is entitled "Analyzing Students’ Text within Critical Thinking, Critical Literacy, and Appraisal Frameworks: Dangers of Texting while Driving ", where in this paper analyze from a text that has to think critically (critical thinking) and a critical framework (Critical Literacy Framework). Analysis is the process done carefully by dividing the problem with through the technical application of analysis and the application of appropriate knowledge. In Critical thinking is a process that involves mental operations such as induction, deduction, classification, and reasoning. In the process of thinking takes place the events analyzed, criticized, and reached conclusions based on careful inference or consideration (Ibrahim and Nur, 2000). This critical activates the ability to do analysis, as well as identify questions that can be text.Keywords: analysis, critical thinking, critical literacy, appraisal, frameworks